2022
DOI: 10.1016/j.jcmgh.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Pathobionts Contribute to Colon Cancer Initiation by Counterbalancing Epithelial Antimicrobial Responses

Abstract: Invasive pathobionts contribute to cancer initiation during a key time frame by counterbalancing autophagy and oxidative stress in the colonic epithelium. Monitoring gut microbiota and antimicrobial patterns may help identify the window of opportunity for intervention with bacteriumtargeted precision medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…HtrA proteins have also been detected in H. influenzae , H. pylori , C. jejuni , and A. actinomycetemcomitans [10] . A recent study indicates that HtrA proteins in H. pylori are related to the risk of gastric cancer and a subsequent study suggested a time-specific host–microbe relationship probably exists in some gastrointestinal pathogens [61] , [62] . In Gram-negative bacteria, OMVs seem to be an effective means of translocation for virulence-associated HtrAs.…”
Section: The Versatile Roles Exhibited By Htra Proteins In Bacteriamentioning
confidence: 99%
“…HtrA proteins have also been detected in H. influenzae , H. pylori , C. jejuni , and A. actinomycetemcomitans [10] . A recent study indicates that HtrA proteins in H. pylori are related to the risk of gastric cancer and a subsequent study suggested a time-specific host–microbe relationship probably exists in some gastrointestinal pathogens [61] , [62] . In Gram-negative bacteria, OMVs seem to be an effective means of translocation for virulence-associated HtrAs.…”
Section: The Versatile Roles Exhibited By Htra Proteins In Bacteriamentioning
confidence: 99%
“…The repression of autophagy by E. coli , in turn, led to increased generation of ROS and epithelial hyperproliferation. However, as the dysplasia tissue progressed, autophagy was upregulated to eradicate the pathogen, suggesting an E. coli -independent tumor growth in the late stage of CRC development [ 104 ]. In line with this, the only time window when antibiotic intervention exhibited a tumor-suppressive effect was in the middle stages of tumor development [ 104 ].…”
Section: Autophagy Coordinates Cellular Adaptation To Stress In the P...mentioning
confidence: 99%
“…The growth of colibactin E. coli is greatly enhanced with increased epithelial oxygenation, which is highly associated with tumorigenesis ( Cevallos et al., 2019 ). E. coli may also develop tumorigenicity in a healthy human gut over time and may contribute to CRC by adjusting host’s epithelial autophagy and oxidative stress response ( Yu et al., 2021 ). However, invasiveness of E. coli can be countered by PTPN2 gene which encodes for T-cell protein tyrosine phosphatase (TCPTP) ( Shawki et al., 2020 ).…”
Section: Gut Microbiota Dysbiosis In Eocrcmentioning
confidence: 99%